Pengaruh Variasi Temperatur Pengeringan Terhadap Daya Kilap Cat Pada Komponen Kendaraan Bermotor: Effect of Variation in Drying Temperature on Paint Glossy on Motor Vehicle Components - Sopiyan; Muhammad Iqbal; Ferry Budhi Susetyo (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2022)
Varies drying temperature will be carried out to see the characteristics formed such as gloss, bending ability, and adhesion resistance. The SPCC plate was cut and then carried out an epoxy painting process and dried. Then proceed with painting by giving black color and drying. Then proceed with the provision of varnish with a composition of 1:0.3 varnish and solvent. After completion, it is then baked in an oven with temperature variations of 40, 60, and 80ËšC for 25 minutes. The temperature of 40ËšC produces the highest gloss, which is 98.9 GU, good adhesion because there is no peeling paint and good bending results because there are no cracks.